Reformulation of the compensation mechanism for fulfilling the rights of victims of corruption in Indonesia - Hasrul Halili; Totok Dwi Diantoro; Zainal Arifin Mochtar (Integritas: Jurnal Antikorupsi, 2025)
Corruption, as a criminal act, causes victims. Identifying victims of corruption is not straightforward, as they can be direct or indirect. Victims of corruption include the state, groups, and individuals in society. This distinction characterizes corruption victims differently from victims of other crimes. Law enforcement efforts against corruption mainly focus on punishing perpetrators. The recovery of state losses is usually limited to compensation payments, which cover the proceeds of crime received by the perpetrator, rather than the full amount of the loss suffered by the state. Meanwhile, victims who are groups and individuals within society are often overlooked in the legal system. To date, Indonesia has not implemented a practice of compensating communities—both groups and individuals—who are victims of corruption. This research is a juridical-normative study. It uses both a statutory approach and a conceptual approach. The statutory approach examines the mechanism for compensating corruption victims in the Civil Code (KUHPerdata), Criminal Procedure Code (KUHAP), and other relevant laws and regulations. The conceptual approach explores the idea of victim recovery in corruption cases. The study finds that Indonesian law currently offers three ways for victims of corruption to seek compensation: civil lawsuits, joining civil suits with criminal cases, and restitution. However, existing regulations lack a clear and specific mechanism to ensure victims' rights are fully met. A dedicated compensation mechanism, aligned with the nature of corruption victims and their losses, is necessary in the Draft Law on Corruption (RUU Tipikor).